A metamaterial cylindrical shell with multiple graded resonators for broadband longitudinal wave attenuation - Yao, Jingyi; Xu, Ke; Yao, Dunhui; Yao, Lingyun (Frontiers in Physics, 2023)
This paper investigates a metamaterial cylindrical shell with local resonators for broadband longitudinal wave mitigation. A three-component phononic crystal metamaterial cylindrical shell which opens local resonant bandgaps at low frequency is formed by periodically inserting a plumbum column coated with soft rubber into an ordinary cylindrical shell. First, the governing equations of elastic wave propagating in cylindrical shell structures are derived by transforming the coordinate. Then, numerical models of the metamaterial cylindrical shell are established and the dispersion relation and vibration transmission characteristics of this structure are calculated by using Finite Element Method (FEM). Finally, in order to further broaden the band- gaps and its strong suppression range, a multiple graded-resonators metamaterial cylindrical shell with three different local resonators is also proposed. These local resonators have different start frequency and location of longitudinal waves bandgaps, so they can be combined to form a wider joint bandgap. Numerical results show that this kind of multiple graded-resonators metamaterial cylindrical shell has a good vibration suppression effect on the longitudinal wave in the range of about 180Hz to 710Hz and the best effect of vibration suppression can reach to -40dB. In addition, the experimental results of vibration transmission characteristics show a good agreement with the numerical results. This work can provide a new idea and method for acoustic metamaterials to obtain broadband and low frequency bandgaps for cylindrical shell structure.